Mudanças estruturais da economia mineira e do restante do Brasil: uma análise de insumo-produto para o período 1996-2003 - Rafael Morais de Souza; Fernando Salgueiro Perobelli (Nova Economia, 2009)
The input-output matrix is a framework widely used to analyze the productivity structure and the industry interdependence both in national and regional terms. Thus, it is an important feature in the planning process. However, the construction is costly and the publication, sometimes, is made with a lag. Therefore, this paper upgrades the input-output matrix for Minas Gerais State and the rest of Brazil (BDMG and FIPE, 2002) for the period between 1997 and 2003. Based on those matrices, it will be possible to analyze the changes occurred on Minas Gerais and in the rest of Brazil. In order to verify the characteristics of Minas Gerais State we will use the production multiplier and the idea of backward and forward linkages.